Faddeev–Jackiw and the improved methods in quantization of the superconductive system - Huang, Yong-Chang; Yi, Li-Xi (Annals of physics, 2010)
In this paper, we give the overview on Faddeev–Jackiw method and its improved one, as well as the relative studies recently and realize quantization of the superconductive system by the two methods, we get the same results by the two disposal methods. Furthermore, at convenience of the familiar study in this system, we take it as the application example and compare the two methods by dealing with this system from different aspects, demonstrate the improved Faddeev–Jackiw method is effective and significative, and represent the superiorities of the improved Faddeev–Jackiw method. We show that the improved method may simplify investigations of different complicated constrained systems.